Understanding the Role of Corporate Social Responsibility on Internal Customer Satisfaction for Sustainable Business Strategy; A Qualitative Research in the Aviation Industry - Ün, Cigdem; Türk, Abdullah (My University, 2023)
In industrial life, where competition is increasingly intense in the globalization process, the efforts of companies to gain an advantage differ. In the 21st century, where competition over economic output and growth and profitability alone does not make a difference, corporate social responsibility projects and strategies to compete by gaining social legitimacy comes to the fore. The inimitable aspect of Human Resources, which is the most valuable resource for a business, has led to the need for deep and different studies on the importance of internal customers. These early-recognizing businesses take measures to retain talented employees, making a difference in competition with internal resources. Social responsibilities, which are the responsibilities of organizations to their employees, their environment, and consumers, form the basis of competition and sustainable strategies today. Based on this basis, the research focusing on the role of corporate social responsibility projects on internal customer satisfaction in the aviation industry wants to reveal organization-based outputs. This qualitative research aims to open a social window to competitive advantage with corporate social responsibility strategies; It is concerned to create an important value to understand the role of the institutions that produce and manage sustainability projects that are sensitive to the environment and society. In this context, qualitative research was conducted with 24 middle and senior managers working at the management level of airline companies operating in Turkey. Within the scope of the research, 7 open-ended questions were asked. All collected data were analyzed using the Maxqda 20 program. Content analysis, which is one of the qualitative research methods, was used in the research and the connection relationship of the parts obtained as a result of the analysis was conveyed according to the direction of configuration.